Reactivation of Ramadi-Musaiyib Fault-Najd Faults System, Iraq - Ramthan, Ali; Chlaib, Hussein Kh. (Iraqi Journal of Science, 2024)
Nine earthquakes inside Mesopotamia Plain from 2016 to 2018 were analyzed. Three seismic networks have been relied on to relocate these events and know their responsible fault. These networks are; Mesopotamian Seismological Center, Al-Refaei Seismic Array and Iranian Seismological Center. The results showed that the root mean square (RMS) values for all relocated events ranged between 0.002-0.997. The results of the error ellipse ranged from 0.24 - 4.17 km with longitude and 0.76 - 8.24 km with latitude. The new locations of these events are on or near the Ramadi-Musaiyib Fault. This means that the Ramadi-Musaiyib Fault, which belongs to the Najd fault system, is currently in reactivation.